1970
DOI: 10.3329/bjpt.v17i1.5394
|View full text |Cite
|
Sign up to set email alerts
|

Some freshwater phytoplankton as new reports and one new forma from Bangladesh

Abstract: Eight newly recorded taxa of freshwater phytoplankton from Bangladesh have been described in the present paper. Of these, 3 species are from Cryptomonadales, 2 species from each of Volvocales and Euglenales and one species from Chromulinales. In addition one new forma of Pediastrum duplex Meyen var. duplex fa. nagdaensis M.A. Alfasane, M.S. Islam & M. Khondker fa. nov. (Chlorococcales) has also been described in this account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The occurrence of Euglenoid algae are very common in different aquatic habitats of Bangladesh (Alfasane et al, 2010(Alfasane et al, , 2021aGani et al, 2012;Alfasane and Khondker, 2007;Khondker and Alfasane, 2005;Islam and Alfasane 2002, 2003, 2004Islam and Muniruzzaman, 1981). In a recent study on the algae of Surma river in Sylhet, a good number of samples showed the presence of euglenoid algae in this river.…”
Section: Introductionmentioning
confidence: 98%
“…The occurrence of Euglenoid algae are very common in different aquatic habitats of Bangladesh (Alfasane et al, 2010(Alfasane et al, , 2021aGani et al, 2012;Alfasane and Khondker, 2007;Khondker and Alfasane, 2005;Islam and Alfasane 2002, 2003, 2004Islam and Muniruzzaman, 1981). In a recent study on the algae of Surma river in Sylhet, a good number of samples showed the presence of euglenoid algae in this river.…”
Section: Introductionmentioning
confidence: 98%
“…Studies on the members of Euglenophyceae have been made from different fresh water of habitats of Sylhet Division of Bangladesh. So far, there are large number of taxonomic studied of different species of Euglenophycean members were reported (Alfasane and Khondker, 2007;Alfasane et al 2010;Gani et al 2012. Khondker andAlfasane, 2005;Islam and Alfasane 2002, 2003, 2004Islam and Muniruzzaman, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are planktonic and commonly called cryptomonad algae. In Bangladesh, a number of studies were carried out on this phytoplankton (Islam and Khondoker, 1997;Khondoker et al, 2007;Alfasane et al, 2010;Gani et al, 2014). So far, a total of 9 genera and 19 species were reported (Ahmed et al, 2009).…”
Section: Introductionmentioning
confidence: 99%